2009
DOI: 10.1007/s11664-009-0897-x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Growth of Non-Uniform Arsenic Profiles in Silicon Reduced-Pressure Chemical Vapor Deposition Epitaxial Layers

Abstract: An empirical model of As surface segregation during reduced-pressure chemical vapor deposition Si epitaxy is presented. This segregation mechanism determines the resulting doping profile in the grown layer and is here described by a model of simultaneous and independent As adsorption and segregation versus incorporation. The model quantifies this mechanism with enough detail to be successfully applied to the accurate growth of different profiles, including the ascending x À2 doping profiles. For rapidly descen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The background step-like As doped profile was epitaxially grown by CVD on 4-inch <100> n-type Si wafers at a reduced pressure of 60 Torr, and a temperature of 800 "C. As a consequence of As surface segregation during epitaxy a profile must be grown by first depositing a desired amount of As on the Si surface and then growing Si with a well-tuned arsine partial pressure [8]. By doing so, a section with flat doping will be grown and to obtain a drop in doping the deposited As must be ex-situ chemically removed [9].…”
Section: E Xperimenta L Proced Uresmentioning
confidence: 99%
“…The background step-like As doped profile was epitaxially grown by CVD on 4-inch <100> n-type Si wafers at a reduced pressure of 60 Torr, and a temperature of 800 "C. As a consequence of As surface segregation during epitaxy a profile must be grown by first depositing a desired amount of As on the Si surface and then growing Si with a well-tuned arsine partial pressure [8]. By doing so, a section with flat doping will be grown and to obtain a drop in doping the deposited As must be ex-situ chemically removed [9].…”
Section: E Xperimenta L Proced Uresmentioning
confidence: 99%
“…However, using arsine is challenging due to its strong tendency to segregate on the surface and subsequent auto-doping behavior. Past work has shown that these properties can be controlled and applied with benefit to create special doping profiles [ 8 , 9 ]. Here a technique is developed for a controlled segregation, removal and auto-doping of As to obtain the required very lowly-doped profiles.…”
Section: Introductionmentioning
confidence: 99%